(untitled) (Praxis Educativa, 2026)
This exploratory study investigated the use of ChatGPT as a support tool for academic writing in higher education, with the aim of developing AI-assisted tutoring teaching strategies and promoting critical analysis of information. The methodology involved an experimental group (A) that used ChatGPT and a control group (B), both in the context of the Faculty of Psychology at UBA. The results indicated that the experimental group showed good performance in written productions, evidencing a development of metacognitive skills and critical analysis. It is concluded that AI, used reflexively, can enrich teaching and learning practices, although the biases and limitations of algorithms, as well as of the different AI models, must always be considered. It highlights the importance of fostering critical thinking and formative evaluation in hypermediated environments.